Design, Fabrication, and Characterization of 3D-Printed Multiphase Scaffolds Based on Triply Periodic Minimal Surfaces - Vigil, Josette; Lewis, Kailey; Norris, Nicholas; Karakoç, Alp; Becker, Timothy A. (Advances in polymer technology, 2024)
The present work investigates the influence of material phases and their volume fractions on the elastic behavior of triply periodic minimal surface (TPMS) scaffolds for the potential modeling of bone scaffolds. A graphical tool using TPMS functions, namely Schwarz-D (diamond), gyroid, and modified gyroid, was developed and used to design and additively manufacture 3D multiphase scaffold models. A PolyJet, UV-cured 3D-printer system was used to fabricate the various TPMS scaffold models using three polymer materials with high, medium, and low stiffness properties. All TPMS models had the same volume fractions of the three polymer materials. Final models were printed into cylinders with a diameter of 20 mm and a height of 8 mm for mechanical testing. The models were subjected to compressive and shear testing using a dynamic mechanical analysis rheometer. All samples were tested at physiologically relevant temperature (37°C) to provide detailed structural characterizations. Microscopic imaging of 3D-printed scaffold longitudinal and cross sections revealed that additive manufacturing adequately recreated the TPMS functions, which created anisotropic materials with variable structures in the longitudinal and transverse directions. Mechanical testing showed that all three TPMS 3D-printed scaffold types exhibited significantly different shear and compressive properties (verifying anisotropic properties) despite being constructed of the same volume fractions of the three UV-printed polymer materials. The gyroid and diamond scaffolds demonstrated complex moduli values that ranged from 1.2 to 1.8 times greater than the modified gyroid scaffolds in both shear and compression. Control scaffolds printed from 100% of each of the three polymers had statistically similar mechanical properties, verifying isotropic properties.